Writing (at) the End: Thomas Pynchon’s Bleeding Edge - Brian Chappell (Transatlantica)
In work spanning six decades, Thomas Pynchon has depicted a plural world reduced to mechanization, automation, and control. In doing so he has done more than any American author to reveal to readers the posthuman future. This essay seeks Pynchon’s human(e) response to these eschatological forces. It does so by examining how Pynchon concludes his works. Referring to Peter Rabinowitz’s theory of endings, this essay argues that at the conclusion of his novels, Pynchon takes on a voice that speaks more urgently than the pluralism and polyphony that permeate his pages. This move from noise to clarity is a move from spiritualism to spirituality. Even though possibilities are diminishing, and the end seems near, there remains the opportunity for communion, shared vulnerability, family, and friendship. This essay focuses on how this move transpires in Bleeding Edge, a novel that presents, potentially, the culmination of historical-eschatological movements toward reduction and domination. But the novel concludes with an extended meditation on family love and female friendship, in a way that conveys Pynchon’s source of hope. Focusing on his endings reveals an enduring humanism at the core of Pynchon’s work that can fuel further study in the age of terror, surveillance, domination, and dehumanization.